Diseño de un mortero con arcillas y cemento portland tipo i para su uso en impresoras 3d - Chimbolema Morocho, Silvia Piedad (2017)
At present, 3d printers are used to manufacture all kinds of civil works faster, this technology saves 60% in materials and 70% in production time; 80% of labor costs. However, the main constraint to use this technology in our country is to have a material with the characteristics that adapt to these equipments. This research aims to obtain a mortar, which has good characteristics of setting, resistance and workability, using clay from the region, obtained from local mines, cement and additives for use in 3d printers. In order to evaluate the physical, chemical and mechanical properties of the new material, a comparison was made between three types of clays used in this study. Resistances of 15 Mpa were obtained, curing times less than 3 hours, liquid limit of 24%, and plastic limit of 14%, moisture content 25%, silicon oxide of 66%, aluminum oxide 26% and the retraction limit of 64%. This new material could be used to build homes as an economic and innovative solution for the construction industry. The material´s retraction is an aspect that requires greater investigation.